Does commitment to environmental self-regulation matter? An empirical examination from China. Issue 5 (15th June 2015) - Lin, Han; Zeng, Saixing; Ma, Hanyang; Chen, Hongquan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop a better understanding of the mechanisms by which symbolic commitment to self-regulation influences corporate environmental performance through the adoption of substantive actions. Design/methodology/approach – Using a sample of Chinese listed private firms in manufacturing sectors, this paper empirically investigates whether and how corporate symbolic commitment to environmental self-regulation really improves the consequences of corporate activities with respect to environmental issues under the current Chinese context. A moderated mediation analysis is employed to test the hypotheses and examine the relationships proposed in the research framework. Findings – The authors argue that making a commitment to environmental self-regulation could motivate firms to implement effective means of being green. The intriguing and robust results show that firms with higher ranking environmental commitment are more likely to use political connections to obtain resources (green subsidies), and then improve environmental performance. Practical implications – The results of this study provide a snapshot of the mechanism between symbolic promises and real outcomes. Originality/value – The authors theorize about and test both direct and indirect effects of commitment to self-regulation on real outcomes which provide empirical evidence for the incipient but growing understanding of self-regulation.